Managing information complexity using system dynamics on construction projects. Issue 3 (3rd March 2016) - Khan, Khurram Iqbal Ahmad; Flanagan, Roger; Lu, Shu-Ling
Abstract : The increase in e-commerce, the digitisation of design data and the interchange and sharing of information have made the construction sector more reliant upon IT infrastructure and systems. The design and production process is complex, dynamic, interconnected and dependent upon greater information mobility, requiring seamless exchange of data and information in real time. Small- and medium-sized enterprises (SMEs), in particular, specialty contractors, can utilise cost-effective collaboration technologies, such as cloud computing using software as a service, to help in the effective transfer of information and data. The system dynamics (SD) approach gives a better understanding of the dynamics of complex systems. SD methodology is used as a modelling and analysis tool to understand and identify the key drivers in the absorption of cloud computing for SMEs. The aim is to determine how the use of SD can improve the management of complexity of information flow, leading to improved performance for SMEs. SD is shown to be a viable tool to manage information complexity using cloud computing for performance improvement in construction.